Assessment of Seasonal Stress for the Production of F1 Hybrid Rice Seed through CMS Breeding Technology - Pal, Riya; Tah, Jagatpati (International Journal of Bio-resource and Stress Management, 2013)
IR58025A as A-line, and KMR-3 as R-line were procured from the State Rice Research Station, Chinsurah, Hooghly which are grown in the research plot in the Crop Research Farm under the Department of Botany of the University of Burdwan following the norms of CMS breeding layout design. Hybrid rice is the commercial rice crop from F1 seeds of cross between two genetically dissimilar parents. Good rice hybrids have potential of yielding 15-20% more than the best inbred variety grown under similar conditions. At present there are three types of hybrid seed production system based on the number of parental lines involved viz. A-line (CMS-line), B-line (Maintainer line) and R-line (Restorer line).